2014
DOI: 10.1001/jamapsychiatry.2014.1025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Family Therapies for Adolescent Anorexia Nervosa

Abstract: IMPORTANCE Anorexia nervosa (AN) is a serious disorder with high rates of morbidity and mortality. Family-based treatment (FBT) is an evidence-based therapy for adolescent AN, but less than half of those who receive this approach recover. Hence, it is important to identify other approaches to prevent the development of the chronic form of AN for which there is no known evidence-based treatment.OBJECTIVE To compare FBT with systemic family therapy (SyFT) for the treatment of adolescent-onset AN. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
225
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(251 citation statements)
references
References 38 publications
(44 reference statements)
12
225
1
9
Order By: Relevance
“…Along with low engagement rates in the intervention, the study was also characterized by high drop-out rates, i.e., over 50% in the control group and 65.6% in the intervention group. These rates exceed drop-out rates of both targeted intervention trials for ED in general [48,49] and of those reported for family-based treatment trials for AN which average between 15-25% [50][51][52].…”
Section: Limitationscontrasting
confidence: 58%
“…Along with low engagement rates in the intervention, the study was also characterized by high drop-out rates, i.e., over 50% in the control group and 65.6% in the intervention group. These rates exceed drop-out rates of both targeted intervention trials for ED in general [48,49] and of those reported for family-based treatment trials for AN which average between 15-25% [50][51][52].…”
Section: Limitationscontrasting
confidence: 58%
“…However, patients in the FBT arm spent fewer days in the hospital, produced lower treatment costs and gained weight faster at the beginning of treatment. Furthermore, patients with more severe obsessive- www.co-psychiatry.comcompulsive symptoms benefitted more from systemic treatment [31].…”
Section: Psychological Approachesmentioning
confidence: 99%
“…It was observed that studies that included only biological indicators, such as BMI and menstruation, had more favorable results, with a complete remission of 50% and 60% of the patients who started treatment. Studies that included psychopathological indicators, such as treatment outcome presented less favorable results, reaching 25%, as in the study by Agras et al 24 .…”
Section: Methodsological Limitationsmentioning
confidence: 90%
“…Several methodological limitations were identified in the studies assessed: lack of description regarding the inclusion and exclusion criteria 29,30 , loss of a significant number of participants (> 25%) during treatment and follow-up 9,24 , lack of clarity regarding the remission criteria or remission assessed exclusively on the basis of biological markers 12,25,[29][30][31] , difficulty in randomizing baseline participants 26,31 , presence of confounding variables, such as the need for hospitalization, the use of antidepressants for the treatment of comorbidities, which were not necessarily controlled in the analyses 18,22,26,27,30,31 and non-probabilistic samples 20,25,29,30 . In only one study no methodological limitations were found 28 .…”
Section: Methodsological Limitationsmentioning
confidence: 99%